Statins Disrupt Macrophage Rac1 Regulation Leading to Increased Atherosclerotic Plaque Calcification - Healy, Abigail (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: Calcification of atherosclerotic plaque is traditionally associated with increased cardiovascular event risk; however, recent studies have found increased calcium density to be associated with more stable disease. HMG-CoA reductase inhibitors or “statins” reduce cardiovascular events. Invasive clinical studies have found that statins alter both the lipid and calcium composition of plaque, but the molecular mechanisms of statin-mediated effects on plaque calcium composition remain unclear. We recently defined a macrophage Rac-IL-1β signaling axis to be a key mechanism in promoting atherosclerotic calcification and sought to define the impact of statin therapy on this pathway. APPROACH AND RESULTS: Here, we demonstrate that statin therapy is independently associated with elevated coronary calcification in a high-risk patient population and that statins disrupt the complex between Rac1 and its inhibitor, RhoGDI, leading to increased active (GTP-bound) Rac1 in primary monocytes/macrophages. Rac1 activation is prevented by rescue with the isoprenyl precursor geranylgeranyl diphosphate. Statin treated macrophages exhibit increased activation of NF-κB, increased IL-1β mRNA, and increased Rac1-dependent IL-1β protein secretion in response to inflammasome stimulation. Using an animal model of calcific atherosclerosis, inclusion of statin in the atherogenic diet led to a myeloid Rac1-dependent increase in atherosclerotic calcification, which was associated with increased serum IL-1β expression, increased plaque Rac1-activation, and increased plaque expression of the osteogenic markers, ALP and RUNX2. CONCLUSION: Statins are capable of increasing atherosclerotic calcification through disinhibition of a macrophage Rac1-IL-1β signaling axis.